BUDAYA ORGANISASI ADAPTIF: STRATEGI MENINGKATKAN KINERJA ORGANISASI DI MASA SULIT - Syaiful Bakhri; Dede Dede (Jurnal Signaling, 2023)
The challenges of an increasingly competitive era make organizations need to look for an approach that is systematic, comprehensive, and adaptive so as to make the organization survive. In addition to the resource factors that support organizational performance, the role of culture as a value and system adopted by all human resources in the organization plays an important role. Organizational culture can be a guide for the organization in carrying out its operations because the truth value also shows the norms adopted in an organization. This study aims to explore the types of culture that are in accordance with the character of increasingly complex challenges for organizations. Qualitative research is used for this research by searching for appropriate literature using an electronic database on organizational culture in the 2018-2022 period which is found in Google Scholar. The results of the study show that implementing an adaptive organizational culture is an effective choice of organizational culture because it allows members to recognize environmental threats and develop solutions to change quickly. In addition, an adaptive organizational culture enables the organization to act in the best interests of the organization by responding appropriately, thereby increasing the organization's chances of survival while enhancing performance.